Pringle Taylor letterbook - Taylor, Pringle, 1796-1884.
Letterbook (87 pages) containing letters relating to Chartism.
Handwritten transcripts.
British army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chartism; Army officers, British